Separation of IGCC syngas by using ZIF-8/dimethylacetamide slurry with high CO2 sorption capacity and sorption speed but low sorption heat. (15th June 2020) - Yang, Ming-Ke; Han, Yu; Zou, En-Bao; Chen, Wan; Peng, Xiao-Wan; Dong, Bao-Can; Sun, Chang-Yu; Liu, Bei; Chen, Guang-Jin
Abstract: An absorption-adsorption hybrid method for separating the integrated gasification combined cycle (IGCC) syngas using ZIF-8/dimethylacetamide (DMAC) slurry was proposed. The viscosity of ZIF-8/DMAC slurries and its sorption performance of pure CO2 were investigated and one optimized slurry with moderate viscosity and high sorption capacity was proposed. Parallel absorption experiments show that the apparent solubility of CO2 in the slurry was doubled compared with that in pure liquid DMAC or propylene carbonate; it even overcomes that in aqueous monoethanolamine solutions at middle to high pressure range. More importantly, the slurry exhibits higher CO2 capture speed compared with conventional absorbents, while its desorption heat is only ∼16 kJ/mol. The equilibrium separation results on H2 /CO2 mixtures using ZIF-8/DMAC slurry show that the selectivity of CO2 over H2 ranged from 22 to 119; it increases with decreasing temperature or pressure, increasing initial gas to slurry ratio or CO2 concentration in feed gas. Only 4 theoretical equilibrium stages are required to achieve a sufficient separation of IGCC syngas. Regeneration test shows that the crystal structure of recovered ZIF-8 remains intact after 6 sorption-desorption cycles. This work provides an efficient method for the separation of IGCC syngas at pressure of 2–5 MPa. Highlights: ZIF-8/DMAC slurry was used to capture CO2 from IGCC syngas. The CO2 solubility in the slurry reach 4.56 mol/L at 1.5 MPa and 298.15 K. The desorption heat of CO2 in ZIF-8/DMAC slurry is only about 16 kJ/mol. The slurry viscosity remains lower than 13 mPa s and CO2 sorption rate is high. CO2 selectivity over H2 of 22–119 is enough for an efficient separation of IGCC syngas.